Medical Diagnosis and the Colour Yellow in Early Modern England - Helen HICKEY (E-REA)
This article will survey the colour yellow in early modern England using resources chiefly from medicine but also literature, sumptuary law, and quotidian culture. In doing so, it interrogates the extent to which this colour changed in symbolism and meaning from the early 15th to the early 17th century. It takes as its starting point humoural theory, which was a vital component of not only medieval but early modern medical diagnosis. The discernment of a person’s underlying disposition relied on knowledge of humoural properties: phlegmatic, sanguine, melancholic or choleric. In especial, the humours were “colour-tagged”, with the choleric temperament usually described in medieval medical treatises as “yellow”.Michel Pastoureau has alerted us to the ambiguity of interpretation the medieval world imposed on particular hues. An examination of colour in early modern England also illuminates the perceptual edges that flow from a society’s chromatic practice, medical understanding and cultural symbolism. Although we cannot assume a transhistorical shared optics of any colour, “yellow”, by its affinity with various bodily byproducts, holds a special place in medical diagnosis. This leads us to question how we might interpret its meanings, both fluid and complex, within early modern England.